School Literacy Movement through Community-Based Reading Corner Assistance in Aek Tapa Village - Annim Hasibuan; Enny Fitriani; Risnawaty Risnawaty (Proceeding of the International Conference on Global Education and Learning, 2025)
The low level of literacy culture remains a significant challenge in improving the quality of education in rural areas. One of the main causes is the limited access to engaging reading materials and the lack of optimal community involvement in supporting school literacy activities. This community service program aims to enhance students’ reading culture through community-based Reading Corner assistance in Aek Tapa Village. The implementation method consisted of several stages, including preparation, socialization, the establishment of a literacy community, the provision of a Reading Corner, reading activity assistance, and monitoring and evaluation. The target participants were elementary school students, teachers, parents, and local community members. The results of the program showed an increase in students’ interest in reading, an expansion of reading collections through community book donations, greater parental involvement in reading activities, and the establishment of a village literacy community that independently manages the Reading Corner. This program demonstrates that collaboration among schools, higher education institutions, village governments, and the community can create a sustainable learning environment that supports the School Literacy Movement.